ZnO Catalyzed Efficient Synthesis of Some New 2-Substituted-4, 6-diarylpyrimidines. (30th October 2012) - Ameta, K. L.; Kumar, Biresh; Rathore, Nitu S.
Abstract : A simple and efficient protocol is developed for the synthesis of 2-substituted-4, 6-diarylpyrimidines from one-pot three-component reaction of 4′-hydroxy-3′, 5′-dinitro substituted chalcones, S-benzylthiouronium chloride (SBT), and heterocyclic secondary amines (morpholine/pyrrolidine/piperidine) in the presence of 15 mol% of ZnO as a heterogeneous catalyst. The present methodology offers several advantages such as being a simple procedure as well as providing excellent yields, and short reaction time. The catalyst is inexpensive, stable, and can be easily recycled and reused for several cycles with consistent activity.